2020
DOI: 10.1093/jac/dkaa197
|View full text |Cite
|
Sign up to set email alerts
|

Determining the optimal dosing of a novel combination regimen of ceftazidime/avibactam with aztreonam against NDM-1-producing Enterobacteriaceae using a hollow-fibre infection model

Abstract: Background MBL-producing strains of Enterobacteriaceae are a major public health concern. We sought to define optimal combination regimens of ceftazidime/avibactam with aztreonam in a hollow-fibre infection model (HFIM) of MBL-producing strains of Escherichia coli and Klebsiella pneumoniae. Methods E. coli ARLG-1013 (blaNDM-1, blaCTX-M, blaCMY, blaTEM) and K. pneumoniae ARLG-1002 (blaNDM-1, blaCTXM-15, blaDHA, blaSHV, blaTEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…A recent hollow-fiber infection model study found that human-simulated dosing of CAZ-AVI 2-0.5 g every 8 h plus ATM 2 g every 6 h over 2 h, or both agents administered as continuous infusions yielded the greatest bacterial killing without emergence of resistance over 7 days. 62 This in vitro study may provide guidance for use clinically while awaiting further studies. Furthermore, the pharmacokinetic/pharmacodynamic (PK/PD) target parameters of this combination against MBL-producing Enterobacterales has yet to be fully elucidated.…”
mentioning
confidence: 95%
“…A recent hollow-fiber infection model study found that human-simulated dosing of CAZ-AVI 2-0.5 g every 8 h plus ATM 2 g every 6 h over 2 h, or both agents administered as continuous infusions yielded the greatest bacterial killing without emergence of resistance over 7 days. 62 This in vitro study may provide guidance for use clinically while awaiting further studies. Furthermore, the pharmacokinetic/pharmacodynamic (PK/PD) target parameters of this combination against MBL-producing Enterobacterales has yet to be fully elucidated.…”
mentioning
confidence: 95%
“…A hollow fiber infection model examining different dosing regimens suggested a preferred regimen of simultaneous administration of ceftazidime/avibactam with aztreonam as opposed to staggered sequential administration, no difference between extended infusion and or standard infusion rate, and possible superiority of 8gm of daily aztreonam. This modelling was based on two New Delhi metallo-β-lactamase Enterobacteriaceae strains [80,81].…”
Section: Avibactam-aztreonammentioning
confidence: 99%
“…The paramount issue is that the optimum pharmacokinetic/pharmacodynamic (Pk/Pd) target for ATM in combination with CZA is still to be determined. According to in vitro models, optimal eradication and resistance suppression may be achieved by administering 8 g instead of 6 g per day of ATM (as continuous or 2-h infusion each 6 h of 2 g) plus 2.5 g each 8 h of CZA [ 78 ]. Monte Carlo simulations run from a PK analysis of clinical samples of MBL-producing isolates from highly comorbid patients demonstrate that standard dosage (CZA 2.5 g and ATM 2 g every 8 h, the most frequent according to our systematic review) fulfilled the time-dependent Pd targets for these agents [ 79 ].…”
Section: Discussionmentioning
confidence: 99%